2020
DOI: 10.3390/plants9050657
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Potential, Photosynthetic and Antioxidant Response to Arsenic-Induced Stress of Dactylis glomerata L. Sown on Fly Ash Deposits

Abstract: Arsenic (As) from coal fly ash can be released into soil/groundwater, presenting a global threat to the environment and human health. To overcome this environmental problem, phytoremediation represents an urgent need, providing ‘green’ cleanup of contaminated lands. The present study focused on As concentrations in fly ash and plants, evaluation of phytoremediation potential of Dactylis glomerata sown on fly ash deposits together with its photosynthetic activity, and oxidative and antioxidative response to As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 140 publications
3
36
0
Order By: Relevance
“…This is why it is of the utmost importance to choose the right plants; those that are pollution tolerant and are the best at growing naturally [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Previous research has shown that invasive herbaceous species like Dactylis glomerata L., Ipomea carnea Jacq., Saccharum spontaneum L. , Cynodon dactylon L., and Calamagrostis epigeyos L. [ 17 , 21 , 22 , 23 ], but also invasive woody species such as Robinia pseudoacacia L., Betula verrucosa Ehrh., Salix alba L., Salix fragilis L., Populus tremula L., Populus nigra L., Populus alba L., Pinus sylvestris L., Alnus glutinosa (L.) Gaertn and Alnus incana (L.) Moench, Paulownia sp. have exceptional adaptive potential to survive under such extreme conditions, i.e., they do not require any specific habitat management for survival, and can play a significant role in the decontamination and amelioration of such habitats, especially during the initial stages of the revegetation process.…”
Section: Introductionmentioning
confidence: 99%
“…This is why it is of the utmost importance to choose the right plants; those that are pollution tolerant and are the best at growing naturally [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Previous research has shown that invasive herbaceous species like Dactylis glomerata L., Ipomea carnea Jacq., Saccharum spontaneum L. , Cynodon dactylon L., and Calamagrostis epigeyos L. [ 17 , 21 , 22 , 23 ], but also invasive woody species such as Robinia pseudoacacia L., Betula verrucosa Ehrh., Salix alba L., Salix fragilis L., Populus tremula L., Populus nigra L., Populus alba L., Pinus sylvestris L., Alnus glutinosa (L.) Gaertn and Alnus incana (L.) Moench, Paulownia sp. have exceptional adaptive potential to survive under such extreme conditions, i.e., they do not require any specific habitat management for survival, and can play a significant role in the decontamination and amelioration of such habitats, especially during the initial stages of the revegetation process.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, photochemical efficiency was lowest in plants grown on CFA without the addition of SS. In the work Gajić et al [83], the Fv/Fm ratio was also low in Dactylis glomerata L. growing on fly ash. Low values of the Fv/Fm ratio in the range of 0.429 to 0.691 were also reported in herbaceous plants, shrubs and trees, including Cirsium arvense, Epilobium collinum, Crepis bienis, Eupatorium cannabinum, Verbascum phlomoides, Calamagrostis epigejos, Oenothera biennis and Festuca rubra, growing on fly ash [84][85][86][87].…”
Section: Discussionmentioning
confidence: 88%
“…It is a fast-growing, loose-cluster species with a well-developed bundle root system, common to Europe, Asia, and North Africa. It is resistant to low temperatures, drought, and diseases [ 93 , 94 ]. It is also an energy grass, with biomass production reaching from 11 to 13 Mg d.m.…”
Section: Methodsmentioning
confidence: 99%